A Novel Information Hiding Approach using Selective Quantization Technique in Video Coding - Hau, Joan; Tew, Yiqi; Tan, Li Peng (Society of Visual Informatics, 2024)
This research examines the different areas of information hiding in current and emerging video compression standards. In the subsequent sections, we provide a detailed comparison of these techniques based on partition modes, prediction units, transform coding, and syntax elements. It shows the engineer and the reader that none of the methods are perfect but are the best for selected applications. We also consider the new video coding standards that have recently appeared, H.266/Versatile Video Coding (VVC) and H.265/High-Efficiency Video Coding (HEVC) and stress the fact that information hiding is critical in attaining such high compression efficacy. To facilitate the reader's understanding of all the relative information, the table that provides the analysis of each technique is presented in the form of a simple listing containing information about each technique's advantages, disadvantages, impacts, and practical applications. The current resource is intended to assist researchers and practitioners in optimizing information hiding for improved video compression. The study's outcome can contribute to enhancing knowledge of information hiding and the new developments of information hiding in video compression beyond what current research offers now, as well as provide a foundation for fresh advances in the field. Further, it is introduced to selective quantization techniques as the approach to information hiding. This method also minimizes this distortion while putting the information into the compressed stream. Finally, we evaluate the performance of this introduced approach towards information hiding capacity and maintaining video quality, with the potential to inspire further research and development in the field.